Using Knowledge and Evidence in Health Care : Multidisciplinary Perspectives - Champagne, François; Lemieux-Charles, Louise (Book collections on Project MUSE., 2004)
The contributors to Using Knowledge and Evidence in Health Care seek to broaden our understanding of the complexity involved in health care decision-making by integrating social science knowledge.